A Review of Latent Fingerprint Developed Powder from using Natural Materials - Krushnai. J. Parkale,; Manjushri. S. Bagul, (International Journal of Scientific Research in Science and Technology, 2024)
The fingerprint development technique is one of the oldest methods used in forensic science and is a common method of identifying perpetrators. [1] Different powder methods have been accounted for the development of latent fingerprints on various surfaces in the literature, such as lead, titanium oxide, Rhodamine B dye etc., all powders mentioned had been used for the development of latent fingerprints. Some of these methods using powders when exposed to humans, may lead to health problems, and also these methods are expensive in nature [2]. Various fingerprint powder preparations used for fingerprints have a color or contrast and a sticky material for good adhesion [3]. The goal of this review is to compile the research works done by various experts to identify commonly available, everyday materials as fingerprint powders such materials from various categories such as food powders, plant materials, minerals, cosmetics, carbon-based materials, and miscellaneous powders [1]. The powder method is a quick and easy approach to the development of latent fingerprints on porous and nonporous surface [4]. proposing a new powder method, which is simple, nontoxic to human health, cheap in nature, and as well can be utilized for the development of latent fingerprints on various contrast surfaces [2].
Keywords: Fingerprint; Natural Powder; Porous Surface; Non Porous Surface